Empowerment of â€œProspering Mosqueâ€ with Islamic Activity to Increase Psychological Awareness in The Practice of Religious Tolerance - Saliyo Saliyo (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
This study aims to empower the mosque with Islamic activities in order to increase psychological awareness in the practice of religious tolerance. The method used in this research using Participatory Action Research (PAR) method. The Participatory Action Research (PAR) study was used to demonstrate a community with a dialogue approach and active involvement of researchers in order to increase psychological awareness and public confidence in the act. The steps taken by researchers in conducting research methods Participatory Action Research (PAR) researchers do learning in action, exploration problems, know the actors who work in the field, and understand the system. The results of the Participatory Action Research (PAR) study with the residents in order to prosper the mosque embody the practice of religious tolerance with Islamic activities in the form of performing id - al-Adha prayers and sacrificing qurban, reading shalawat berzanji, Islamic studies on Sunday morning, orphans' donations, and prayer at the mosque. These activities are arranged in order to increase psychological awareness by transforming awareness of tolerance between and interreligious.